A study on students’ difficulties in conducting research / Alif Akram Mohammad, Harry Ajang and Jeriemy Christopher Cheri - Mohammad, Alif Akram; Ajang, Harry; Christopher Cheri, Jeriemy (2010)
Our study was mainly created for students who majority taking Research Methodology as their main subject. Research Methodology as in Diploma in Public Administration is called Research Methodology and its code is PAD340. Meanwhile for Bachelor in Administration Science, the codes for research paper are dividing into two into code. The first one is ADS 501 which is for Proposal and another is ADS 554 which is for the Research paper.This subject is important as it is a main subject for Diploma in Public Administration and Bachelor in Administration Science students. It is compulsory to do the research in order for the students to graduate.